Negative magnetization and exchange bias effect in Fe-doped CoCr2O4. Issue 13 (September 2018) - Li, C.L.; Yan, T.Y.; Barasa, G.O.; Li, Y.H.; Zhang, R.; Fu, Q.S.; Chen, X.H.; Yuan, S.L.
Abstract: Polycrystalline ceramics of Co(Cr1- x Fe x )2 O4 (0 ≤ x ≤ 0.12) were experimentally studied based on a series of temperature and time-dependent dc magnetic measurements using different magnetic field histories. Magnetization in field cooling process was continuously decreased for doping content x in the range of 0 ≤ x ≤ 0.04. Remarkable negative magnetization is observed when x reaches to 0.06 and persists up to x = 0.1. Two-sublattice model is established and competition of the two magnetic sublattices is responsible for the phenomenon. The magnetic switching effect is realized just by changing the magnitude of the applied magnetic field and double magnetocaloric effects are obtained. These unique features under low magnetic fields show attractive for application in spintronic devices due to that the magnetic state can effectively be tuned through magnetic field or temperature. Besides, the system exhibits both positive and negative exchange bias fields which are considered to be originating from the unidirectional anisotropy of exchange coupling of antiferromagnetic/ferromagnetic phases and spin reorientation of the two sublattices magnetic moments, respectively.